2018
DOI: 10.1158/1535-7163.mct-17-1176
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Dopamine D2 Receptor Agonist Bromocriptine to Enhance Docetaxel Chemotherapy and Treat Bone Metastatic Prostate Cancer

Abstract: Docetaxel resistance remains a major obstacle in the treatment of prostate cancer bone metastasis. In this study, we demonstrate that the dopamine D2 receptor (DRD2) agonist bromocriptine effectively enhances docetaxel efficacy and suppresses skeletal growth of prostate cancer in preclinical models. DRD2 is ubiquitously expressed in prostate cancer cell lines and significantly reduced in prostate cancer tissues with high Gleason score. Bromocriptine has weak to moderate cytotoxicity in prostate cancer cells, b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
(52 reference statements)
3
16
0
Order By: Relevance
“…In a recent study, we provided the first evidence demonstrating that DRD2 expression is inversely associated with clinical PCa progression. We further identified bromocriptine, a semisynthetic ergot alkaloid, as a potential adjunct therapy to sensitize PCa cells to docetaxel chemotherapy (35). These observations supported the notion that DRD2 agonism may represent a novel strategy to overcome chemoresistance.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…In a recent study, we provided the first evidence demonstrating that DRD2 expression is inversely associated with clinical PCa progression. We further identified bromocriptine, a semisynthetic ergot alkaloid, as a potential adjunct therapy to sensitize PCa cells to docetaxel chemotherapy (35). These observations supported the notion that DRD2 agonism may represent a novel strategy to overcome chemoresistance.…”
supporting
confidence: 66%
“…Although our understanding of the biology of dopamine receptor signaling in cancer progression is still rudimentary and sometimes controversial, mounting experimental and clinical evidence has indicated that the dysregulation of dopamine receptor signaling is associated with the progression of human cancers, including PCa (35,(57)(58)(59)(60). Some epidemiologic studies further suggested a correlation between psychotic disorders in which dopaminergic drugs are applied and the risk of cancer, of particular note, a reduced risk of PCa (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Since dormant cells are known for their resistance against drug treatment, we further investigated the effect of chemotherapy on Wnt5a-induced dormant cells in bone using docetaxel, the most commonly used drug for the treatment of bone metastatic PCa (Banerjee et al, 2007; Yang et al, 2018). First, antimetastatic efficacy of docetaxel in bone metastasis of PCa was demonstrated by the finding that the tumor burden of mice treated with docetaxel was significantly reduced compared with that in the vehicle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mice study, administration of D2 receptor antagonist amisulpride to diabetic mice restored trabecular bone structure to near normal and partially reversed downregulation of lysyl oxidase 31 . Moreover, bromocriptine, a potent D2 agonist has been widely used in the treatment of bone metastatic prostate cancer 32 . Several studies have found that people with the DRD2 rs1800497 T allele had a higher prolactin level during antipsychotics use 20 .…”
Section: Discussionmentioning
confidence: 99%